Atrakcyjność inwestycyjna gmin jako uwarunkowanie konkurencji podmiotów gospodarczych - Wojewódzka, Agnieszka (Attractiveness of Communities as a Factor Affecting Competitiveness of Business Units, 2006)
This article presents the ranking of the best communities in Poland entitled "Gold Hundred of Local Communities in 2003 and 2004". The brainfather of the list is the Regional Research Centre. The register gives substancial information about inhabitants and investors. The paper discusses the differences between capital expenditures of communities in relation to voivodeships. The analysis concerns one hundered affluent communities.There is no doubt that if Polish communities would like to be competitive they should invest a lot of money in their development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 508-514